Functional Magnetic Resonance Imaging. - Voos, Avery; Pelphrey, Kevin (Journal of Cognition & Development, 2013)
Functional magnetic resonance imaging (fMRI), with its excellent spatial resolution and ability to visualize networks of neuroanatomical structures involved in complex information processing, has become the dominant technique for the study of brain function and its development. The accessibility of in-vivo pediatric brain-imaging techniques together with the revolution in modern molecular genetic and epigenetic techniques offers the developmental scientist an unprecedented opportunity to enact a truly developmental perspective, allowing the experimentalist to understand and integrate multiple levels of analysis in the study of developing children. Here, we review how fMRI works along with a critical issue in the use of fMRI to study cognition and its development—the necessity to carefully control movement in the scanner. We then provide a primer on strategies implemented in our laboratory to successfully scan children as young as 4 years of age while they are awake and engaged in cognitive tasks. We conclude with a practical discussion of the potential risks of fMRI and ways to maximize participant safety and comfort.